Is Globalisation Yesterday's News?. Issue 1 (7th April 2017) - Hopkins, A. G.
Abstract : Globalisation is now a fashionable topic of historical research. Books and articles routinely use the term, though often in a loose manner that has yet to realise the full potential of the subject. The question arises as to whether globalisation, as currently applied by historians, is sufficiently robust to resist inevitable changes in historiographical fashion. The fact that globalisation is a process and not a single theory opens the way, not only to over-general applications of the term, but also to rich research possibilities derived in particular from other social sciences. One such prospect, which ought to be at the centre of all historians' interests, is how to categorise the evolution of the process. This question, which has yet to stimulate the lively debate it needs, is explored here by identifying three successive phases or sequences between the eighteenth century and the present, and joining them to the history of the empires that were their principal agents. These phases, termed proto-globalisation, modern globalisation, and postcolonial globalisation provide the context for reviewing the history of the West, including the United States, and in principle of the wider world too.